Evaluation Of The Implementation Of The Supplementary Food Program In The Prevention Of Stunting In Madatte Village, Work Area Pekkabata Public Health Center, Polewali Mandar District - Dini Dwi Pratiwi Chaerul; Amran Razak; Darmawansyah; Muhammad Alwy Arifin; Muhammad Syafar; Syamsuar Manyullei; Anwar Mallongi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Stunting is caused by malnutrition during the growth and early development of children, thus inhibiting physical development, increasing morbidity rates, inhibiting children’s mental development, and can even lead to death. Providing Additional Food (PMT) is an intervention program for toddlers who suffer from malnutrition where the aim is to improve the child’s nutritional status and to meet the child’s nutritional needs so that good nutritional status and nutritional conditions are achieved according to the child’s age. Method: This study uses a qualitative research method with a case study approach. Interviews were conducted with 7 informants, including 2 key informants and 5 supporting informants. Results: The study consisted of human resource input in the implementation of the program consisting of health workers and posyandu cadres who distributed PMT to program targets with a budget from the BOK and the facilities and infrastructure provided were sufficient for the program being run, the program was run through the policies given and had been in accordance with the procedures for provision so that the program ran quite well, only the lack of communication or cooperation between officers in distributing PMT in the field, in recording reporting was quite good and the results of the program evaluation ran smoothly and had a visible impact with an increase in nutritional status figures after the program was implemented, although it had not yet affected the stunting reduction rate. Conclusion: The implementation of the PMT program has been running well and in accordance with the procedures given with a sufficient budget and facilities and infrastructure and the impact obtained after the program was running with an increase in nutritional status figures which will also have an impact on stunting reduction if the program continues to be implemented properly.